Assessing Innovation Patterns and Constraints in Developing East Asia : An Introductory Analysis - Iootty, Mariana (World Bank, Washington, DC, 2019)
This paper sheds light on key innovation patterns and constraints within a selected set of developing East Asian countries (Cambodia, China, Indonesia, the Lao People’s Democratic Republic, Malaysia, Myanmar, the Philippines, Thailand, and Vietnam). It follows a comprehensive approach about national innovation systems while highlighting the supply and demand dimensions of innovation as well as the markets where firms make accumulation decisions for different forms of capital (knowledge capital, human capital. and physical capital). The paper presents a set of empirical exercises drawing from various data sets. The results corroborate the idea of the importance of adopting a broad view of innovation policy and investing in missing complementary factors. Although investment in research and development is key to boost innovation, it is also crucial to have business and regulatory environments that are conducive to overall firm performance and capital accumulation (not only knowledge capital), as they are expected to improve innovation returns. In addition, the results suggest that other innovation inputs aside from research and development matter for innovation activities, such as training for innovative activities, acquisition/licensing of technology, and managerial practices.